2022
DOI: 10.3390/microorganisms10102073
|View full text |Cite
|
Sign up to set email alerts
|

Initial pH Conditions Shape the Microbial Community Structure of Sewage Sludge in Batch Fermentations for the Improvement of Volatile Fatty Acid Production

Abstract: Conversion of wastewater treatment plants into biorefineries is a sustainable alternative for obtaining valuable compounds, thus reducing pollutants and costs and protecting the environment and human health. Under specific operating conditions, microbial fermentative products of sewage sludge are volatile fatty acids (VFA) that can be precursors of polyhydroxyalkanoate thermoplastic polyesters. The role of various operating parameters in VFA production has yet to be elucidated. This study aimed to correlate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Consequently, it comprehensively impacts the fermentation acidification efficiency of the sludge. 22 Research has also confirmed that higher VFAs yields are obtained under alkaline conditions. Therefore, investigating the mechanism of alkali in the combined pretreatment process of rhamnolipids-alkali-thermal is crucial for a comprehensive understanding and application of this technology.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Consequently, it comprehensively impacts the fermentation acidification efficiency of the sludge. 22 Research has also confirmed that higher VFAs yields are obtained under alkaline conditions. Therefore, investigating the mechanism of alkali in the combined pretreatment process of rhamnolipids-alkali-thermal is crucial for a comprehensive understanding and application of this technology.…”
mentioning
confidence: 82%
“…The addition of NaOH not only affects the changes in sludge disintegration, organic matter composition, and dissolution concentration during the pretreatment stage but also influences the characteristics of microbial community in the subsequent anaerobic fermentation stage. Consequently, it comprehensively impacts the fermentation acidification efficiency of the sludge 22 . Research has also confirmed that higher VFAs yields are obtained under alkaline conditions.…”
Section: Introductionmentioning
confidence: 88%